Endovascular superselective embolization of ven of Galen arteriovenous malformations - Tzymeiko, O. A.; Goncharov, A. I.; Orlov, M. Yu.; Lebed, V. V. (Ukrainian Neurosurgical Journal)
Literature sources and our own experience of AVM of vein of Galen treatment in the Romodanov neurosurgical institute are analyzed. It was confirmed that in most cases usage of the only isolated method of treatment not always leads to expected positive result. That is why at modern stage of such complicated vascular anomaly treatment it is expedient to use combination of shunting and endovascular interventions depending on form of clinical course of the lesion.